A Rapid and Efficient Method to Obtain Photosynthetic Cell Suspension Cultures of Arabidopsis thaliana - Sello, Simone; Moscatiello, Roberto; La Rocca, Nicoletta; Baldan, Barbara; Navazio, Lorella (Frontiers in Plant Science, 2017)
Photosynthetic cell suspension cultures are a useful experimental system to analyse a variety of physiological processes, bypassing the structural complexity of the plant organism in toto. Nevertheless, cell cultures containing functional chloroplasts are quite difficult to obtain, and this process is usually laborious and time-consuming. In this work a novel and rapid method to set up photosynthetic cell suspension cultures from the model plant Arabidopsis thaliana was developed. The direct germination of Arabidopsis seeds on a sucrose-containing agarized culture medium supplemented with 0.25 µg/ml 6-benzylaminopurine and 0.5 µg/ml 2,4-dichlorophenoxyacetic acid caused the straightforward formation of green calli at the level of seedling hypocotyls. The subsequent transfer of these calli in liquid culture medium containing the same concentrations of phytohormones and gradually decreasing sucrose levels allowed for the establishment of chloroplast-containing cell suspension cultures, containing functional chloroplasts, in a much faster way than previously described procedures. Pulse amplitude modulation analyses, measurements of oxygen evolution and electron transport rate, together with confocal and electron microscopy observations, confirmed the photosynthetic efficiency of these cell suspension cultures. The described procedure lends itself as a simple and effective way to obtain a convenient tool for a wide array of structural and functional studies on chloroplasts.